Adolescent’s Self-Efficacy for Early Marriage in South Bangka Regency, Indonesia - Antarini Antarini; Putri Rhadiyah; Tesza Permata; Rizka Marcely; Dini Montovani (International Journal of Public Health Science (IJPHS), 2016)
The percentage of married women under the age of 20 years at 13% with a median age of 20.1 years and the median marriage age of first marriage in the rural lower at 19.7. Pregnancy at a very young age correlated with maternal mortality and morbidity. Girls aged 10-14 are five times the risk of dying during pregnancy or childbirth compared to the age group of 20-24 years, while the risk is doubled in the age group of 15-19 years. This study aimed to analyze several variables that affect the self-forming efficacy of early marriages. The research was explanatory research with cross sectional design. The sample size was 241. Data analysis was performed using correlation analysis Somers. There were very weak positive correlation for Verbal Persuasion (r=0.013), very weak negative correlation for Vicarious Experience (r=-0026) and Emotional Arousal (r=-0075), weak negative correlation between Mastery Experience factor (r=-0035) with early marriage.